Cultural Identity and Religious Practice: Challenges for Tibetan Buddhists in China - Uliana Zhambaeva; Bair Zhambaev; Kairat Osmonaliev; Bakyt Kakeshov (Pharos Journal of Theology)
Freedom of religion is a fundamental human right protected by international law and many national constitutions. In China, the Constitution guarantees freedom of religious belief, but the implementation of this right, particularly for Tibetan Buddhists, has been complex and controversial. This study aims to analyse how the socio-religious rights of Tibetan Buddhists are ensured in 21st century China, considering current legislation and political realities. The research employs a comprehensive analysis of official legal documents. The historical systematic method was employed to examine the interrelated sociocultural systems shaping cultural aspects and national identity. The study reveals a complex and evolving relationship between the Chinese state and Tibetan Buddhism. The research identifies state interference in monastic affairs, including restrictions on the size of monastic communities and their political and economic roles. Government attempts to control the reincarnation process of Tibetan Buddhist leaders and the dispute over the selection process for the next Dalai Lama is ongoing, with both the Chinese government and the current Dalai Lama asserting their right to determine the succession. The study notes some instances for compromise, such as the Chinese government's consideration of allowing the current Dalai Lama to visit China and Tibet under certain conditions. The research highlights the need for further studies on the long-term effects of China's religious policies on Tibetan Buddhist culture and identity, as well as the potential for adaptive strategies within the Tibetan Buddhist community in response to these policies.